Ultrafast excited state dynamics in Diindenoperylene films - Hänsel, Marc; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2017)
Diindenoperylene (DIP) is an interesting organic molecular semiconductor as a component in organic solar cells. Here, we studied the ultrafast excited state dynamics of DIP after optical excitation in thin films on sapphire and SiO2 substrates, respectively, using femtosecond (fs) time-resolved second harmonic generation (TR-SHG). Sapphire, an inert and noninteracting substrate, is known to deliver no noteworthily contribution to the SHG-signal; thus, the pure response of DIP to the electronic excitation can be resolved in contrast to the measurements on SiO2. For DIP/sapphire, the initial optical excitation leads to the generation of delocalized excitons, which localize within approximately 100 fs in order to generate singlet molecular excitons (Frenkel excitons) or excitons localized on dimers. These excitons have a lifetime of 470 ± 100 fs. In a subsequent step, they form excimer states, which decay on a time scale of 680 ± 110 ps. For DIP/SiO2, the molecular excitons decay on a faster time scale of 210 ± 95 fs and populate either substrate-mediated trap states or excimer states. The present study provides important insights in the excited states dynamics of DIP on the so far unresolved ultrashort time scale, essential for understanding the photophysics of DIP.
Gesehen am 24.04.2018